2019
DOI: 10.1167/iovs.18-25675
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR Spectroscopy Characterization of Porcine Vitreous Humor in Physiological and Photoreceptor Degeneration Conditions

Abstract: Citation: Elmi A, Ventrella D, Laghi L, et al. 1 H NMR spectroscopy characterization of porcine vitreous humor in physiological and photoreceptor degeneration conditions. Invest Ophthalmol Vis Sci. 2019;60:741-747. https://doi.org/10.1167/iovs. PURPOSE. Qualitative and quantitative analysis of vitreous humor (VH) is important to discriminate between physiological and pathological conditions and may be particularly helpful when using animal models for ophthalmologic research. The aim of the present study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Inhibition of glycolysis and cell stress, confirmed by 1H-NMR vitreous humor characterization in pigs after 30 days of IAA treatment (Elmi et al, 2019), may provoke three types of events: apoptosis, necrosis or autophagy. Further investigations of the mechanisms of cell death could elucidate the toxic effect of IAA on photoreceptor degeneration.…”
Section: Discussionmentioning
confidence: 81%
“…Inhibition of glycolysis and cell stress, confirmed by 1H-NMR vitreous humor characterization in pigs after 30 days of IAA treatment (Elmi et al, 2019), may provoke three types of events: apoptosis, necrosis or autophagy. Further investigations of the mechanisms of cell death could elucidate the toxic effect of IAA on photoreceptor degeneration.…”
Section: Discussionmentioning
confidence: 81%
“…Domestic pigs were weighted and sedated with an intramuscular (IM) injection of Tiletamine-Zolazepam (Zoletil, Virbac, Prague, Czechia) (5 mg/kg). After 15 min, general anesthesia was induced with 8% sevoflurane (SevoFlo, Esteve, Barcelona, Spain), administered through a mask in a 1:1 oxygen/air mixture and maintained with the same halogenated agent (3%) after orotracheal intubation (Elmi et al, 2019). Lactated Ringer infusion was set at a rate of 10 ml/kg/h through the auricular vein (left ear).…”
Section: Surgical Procedures In the Pigmentioning
confidence: 99%
“…Except for the retina, BCAAs were significantly increased in the serum [31,47] and plasma [29] of DR rats. Elmi et al [48] collected vitreous humor from pigs treated with iodoacetic acid (IAA), the porcine model of photoreceptor degeneration. Their results showed that BCAAs were decreased in the vitreous humor in the IAA group, compared to physiological conditions.…”
Section: The Alterations Of Bcaas In Retinopathymentioning
confidence: 99%